Study of symbols in poems of Li Bai - Wu, Tong (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
As an important poet of China, Li Bai occupies an important position in the literary field of China, and even in the world, gradually. And his recurring symbols in his poems, which are closely related to traditional Chinese culture, have divergences in understanding during the process of translation due to cross-cultural differences. So it is intended to learn and reflect on the meanings implicit in their Chinese poems and inspire the beginning poetry translators.